ИННОВАЦИОННЫЕ ПОДХОДЫ ПО ОПТИМИЗАЦИИ РАБОТЫ ГОСУДАРСТВЕННОЙ ПРОГРАММЫ С УЧЕТОМ ЦИФРОВЫХ ПРЕОБРАЗОВАНИЙ (Экономика: стратегия и практика, 2019)
The purpose of this research is to develop innovative approaches to optimize the organizational process of government programs taking into account digital transformation. In this scientific study, the authors conducted a literary review of scientific research in the field of using the advantages of electronic, platform and digital networks. In addition, the authors have proposed new approaches of the organization of work with scholars of the program “Bolashak” based on digital transformations. The research methodology based on the study of primary and secondary materials of Kazakhstan, which collected in the framework of research work on the study of the program “Bolashak”. Three possible scenarios for the optimization of work with graduates of the program “Bolashak” in order to effectively interact and simplify networking proposed. The scientific novelty of the research is provided by the fact that the scientific provisions concerning the use of digital technologies in the interests of accelerated technological modernization of the domestic economy are substantiated and formulated. It was concluded that digitalization becomes a trend for state educational policy. The rapid development of digital technologies creates new opportunities for a single integrated platform.